Resort to Mediation in Maori-to-Maori Dispute Resolution: is it the Elixir to Cure all Ills? - Hond, Mereana (Victoria University of Wellington Law Review, 2002)
Discourse surrounding the Treaty of Waitangi has shifted the Treaty's status from a "simple nullity" to the foundational document of this country. A very specific dimension of Treaty discourse, Maori-to-Maori disputes in the context of Treaty claim settlement, is explored – particularly mediation. The author argues that mediation is far from a cure-all, and should not be used indiscriminately in Maori disputes. Two examples are explored. The Allocation of Commercial Fisheries Settlement presented mediation as a mandatory dispute resolution procedure, undermining the process altogether. The Ngati Maniapoto, Ngati Tama and Crown mediation process failed to provide a level playing field for all parties involved, resulting in continuous alienation. The author concludes that dispute resolution is just one facet of the Treaty discourse, and conversations between institutions, experts, and law-makers should continue regarding how to redefine Treaty principles in a way that does not rip people apart.